Childhood disabilities and the cost of developmental therapies: the service provider perspective - Sabika Shaban (18279019) (2024)
Purpose For children with neurodevelopmental disabilities (CWNDs), early diagnosis that leads to early intervention with regular targeted therapies is critical. In Qatar, private therapy centres that address this demand often have highly exclusive prices restricting families from availing them. This paper examines the challenges faced by families with CWNDs, as well as various financial and systemic obstacles, from the vantage point of these centres, all of which culminate in an extraordinarily high disability price tag for disability families in Qatar. Methods This study is based on qualitative, semi-structured, and in-depth interviews with private therapy centres and developmental paediatricians. Results Therapy centre representatives expressed common struggles in lengthy and cumbersome administration and licencing procedures, difficulty in hiring and retaining high quality staff, and expenses that need to be paid to the state. From their experience, families largely struggle with delayed diagnoses that significantly slow down intervention plans and therapies as well as staggeringly high financial costs with a dearth of funding options. Conclusions We recommend sincere engagement, dialogue, and cooperation between multiple stakeholders; a supportive ecosystem to balance and distribute the demand that includes schools and parents; as well more efficient administrative procedures and recruitment strategies. Other Information Published in: International Journal of Qualitative Studies on Health and Well-being License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/17482631.2024.2345816